Evaluation of oil palm biomass and fast growing timber species as potential solid biofuel - Chin, Kit Ling (2014)
Lignocellulosics have been identified as one of the renewable energy sources. The conversion process for this purpose must be flexible enough to accommodate various types of biomass. Among the numerous methods for converting lignocellulosic biomass into usable energy, direct combustion is still the dominant technology employed by industry. This work evaluates the potential variation of two lignocellulosic biomass available in Malaysia, i.e. oil palm waste and timbers from fast growing species to be utilized as solid biofuel for heat and electricity generation. The study was divided into five parts. The first part evaluates the fuel properties of oil palm biomass (empty fruit bunch (EFB) and oil palm trunk (OPT)), wood from a range of fast growing timber species (Paraserianthes falcataria, Acacia spp.,Endospermum spp. and Macaranga spp.), inclusive and exclusive of bark. These fibres were chosen because of their abundance and readily available. Heating value and ash forming elements are found to be much higher in timbers inclusive of bark than those without. On the other hand, oil palm biomass contains higher ash forming elements and lower heating value than any of the timber species. The study also suggests lignocellulosic in its raw form, is not efficient as raw material for power plant due to its high moisture content, low bulk energy density, high ash content and low ash melting temperature. The second part of the study investigates the effects of torrefaction treatment on the weight loss and energy properties of Paraserianthes falcataria, Acacia spp., Endospermum spp. and Macaranga spp. and oil palm biomass (oil palm trunk and empty fruit bunch). The lignocellulosic biomass was torrefied at three different temperatures 200, 250 and 300 °C, each for 15, 30 and 45 min. Response surface methodology was used for optimization of torrefaction conditions, so that biofuel of high energy density, maximized energy properties and minimum weight loss could be manufactured. The analyses showed that increase in heating values was affected by treatment severity (cumulated effect of temperature and time). It was demonstrated that each biomass type had its own unique set of operating conditions to achieve the same product quality. The optimized torrefaction conditions were verified empirically and applicability of the model was confirmed. For respective types of lignocellulosic biomass, the optimization experiment gave results of HHV and weight loss as follows: 27.96 MJ/kg, 10.12% for Acacia spp.; 19.14 Mj/kg, 6.17% for Paraserianthes falcataria; 27.19 Mj/kg, 13.41%, for Macaranga spp.; 19.68 MJ/kg, 8.09% for Endospermum spp; 23.08 MJ/kg, 9.55% for EFB and 23.22 MJ/kg,14.94% for OPT. These experimental findings were in close agreement with the model prediction. Torrefaction markedly improved the biofuel characteristics except for ash melting which apparently similar to the raw material and was more severe with raw material initially with problematic ash such as EFB and OPT. The subsequent study aims at studying the effectiveness of leaching on removing ash forming elements and on ash melting using water and acetic acid as the extraction agent. Leaching by acetic acid solutions removed most of ash forming elements, both water soluble and insoluble from the selected lignocellulosic biomass. Ash melting characteristics of lignocellulosic biomass under high temperature were considerably improved by both leaching treatment; water and acetic acid leaching. A model comprising leaching parameters and fuel properties for different types of lignocellulosic biomass was established. This model was later employed to predict the optimal leaching conditions for maximized ash removal efficiency without sacrificing the higher heating value (HHV). To generate optimal leaching conditions, the ash removal efficiency was set to a maximum while the HHV was set in the range of not lower than the initial HHV of the respective lignocellulosic biomass. For respective types of lignocellulosic biomass, the optimization experiment gave results of ash removal efficiency and HHV as follows: 68 %, 18.52 MJ/kg for Acacia spp.; 72%, 17.94 Mj/kg for Paraserianthes falcataria; 72%, 18.13 Mj/kg for Macaranga spp.; 81%, 18.58 MJ/kg for ndospermum spp; 85%, 18.53 MJ/kg, for EFB and 63%, 16.21 MJ/kg, for OPT. Part four of the study explores the possibility of combining leaching and torrefaction treatment to create an improved solid biofuel from lignocellulosic biomass. The focus lies on determining the effects of the combination treatments on ash removal efficiency and on ash melting characteristic of the treated biomass. Two possible pathways were implied; applying torrefaction followed by leaching and leaching followed by torrefaction. Incorporating both leaching and torrefaction treatments irrespective of sequence generated a solid biofuel with better fuel properties particularly HHV yield and ash melting temperature compared to singular treatment;torrefaction or leaching treatment. The ash yield reduction from raw biomass ranged 60 – 86%, whereas the ash yield reduction from torrefied biomass ranged 47 – 68%. Leaching prior to torrefaction proved to be a better combination. The final part of the study evaluates the effect of kaolin and calcite addition on the ash melting characteristic, heating value and ash content of the lignocellulosic biomass. The additives addition to selected lignocellulosic biomass with low ash melting temperature, i.e. Acacia spp., Endospermum spp., EFB and OPT The results show that both additives significantly improved the bottom ash melting characteristic with mixed results. Kaolin is a promising choice since it reduced the sintering degree of the ashes with the formation of inorganic elements mixtures mostly held in the ash sediments. In contrast, the presence of calcite helped to increase the ash melting temperature but at the same time induce higher concentration of fly ash in the flue gas. In general, kaolin is more effective than calcite to reduce molten or strong sintering to weak sintering or loose ash at the dose of 0.25 - 0.5 g/g ash while calcite in general require higher dose at dose equal or higher than 0.5 g/g ash. While the concentrations of additives act as a variable to increase the sintering temperature, it also had strong impacts on HHV reduction and ash content increment. In conclusion, fast growing timber species served as a better solid biofuel than oil palm biomass due to higher HHV and less ash forming elements. The high alkali metals (potassium and sodium) mainly consist in oil palm biomass was found to be one of the main factors that create slagging during high temperature combustion. Ash that is with high K/(Ca + Mg) ratio (alkali metals (potassium) to alkaline earth metals (calcium and magnesium) ratio) tend to have low melting temperature. Novelty approach by combining leaching followed by torrefaction treatment on lignocellulosic biomass was found to be able to create the optimal quality solid biofuel with low ash content, high energy density and high ash melting temperature. The ash related problematic lignocellulosic biomasses (oil palm biomass, Acacia spp. and Endospermum spp.) with low ash melting temperature during high temperature combustion can be solved by additional fuel additives; with kaolin as a better ash melting inhibitor than calcite.